Traditional media vs internet-resources: directions of transformation of the national information field - Postalovsky, Alexander V. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the sociological study of the specifics and specifics of the transformation of the national information field. On the basis of many years of empirical data (2003–2015), a structure and a specific alignment of the information field segments (television, radio, newspapers, the Internet, virtual media media), formed at the present time. The place and role of each segment of the national information field in the structure of priorities of the mass audience is determined. The main trends in the development of the information field (mediaconvergence) are revealed. An analysis of the thirteen-year dynamics of the results of sociological monitoring makes it possible to propose a scientific and theoretical hypothesis regarding the further functioning of the means of the national media system in modern conditions. The result of the analysis of actual theoretical concepts in the sociology of the media (E. Toffler, M. Castells, M. McLuhan) and longstanding empirical sociodynamics is the formation of a forecast for further potential directions of the structural transformation of the national information field.
Keywords: national information field; mass media; transformation; means of network virtual media communication; internet; media convergence